Cross-border electricity interconnectors in the EU: The status quo - Gert Brunekreeft; Roland Meyer (Jacobs University Bremen, Bremen Energy Research (BER), 2018)
An important goal of the European Commission is the promotion of the internal energy market (here specifically electricity), which requires sufficient and adequate cross-border interconnector capacity. However, cross-border interconnector capacity is scarce and, more importantly, the progress of interconnector capacity expansion is too slow. As a result, the Commission has proposed several policy measures to accelerate interconnector investment. This paper provides an overview of the policy debate on interconnector expansion and studies two particular points. First, the effects of network regulation on the interconnector investment and the policy proposals to improve the investment incentives, and more specifically, how to deal with risks. Second, we study the policies and effects of capacity remuneration mechanisms (CRMs) on the use of and the need for cross-border interconnector capacity.
Keywords: L94; L51; D47; 330; electric utilities; regulation; market design